Analisis Faktor Trust dan Price Discount Bagi Pengguna Traveloka Dampaknya terhadap Kepuasan Konsumen dan Loyalitas Konsumen - Yunice Bili (CV. Syntax Corporation Indonesia, 2020)
This study aims to examine the analysis of trust factors and price discounts for Traveloka users, their impact on customer satisfaction and consumer loyalty. The study was conducted on 97 respondents who use Traveloka services, especially flight tickets. The results of this study indicate: 1). Trust variable (X1) with customer satisfaction (Y1) is proven to have a significant effect on customer satisfaction, 2). Price discount variable (X2) with customer satisfaction (Y1) is not proven to have a significant effect on customer satisfaction, 3). Trust variable (X1) with consumer loyalty (Y2) is not proven to have an effect and is significant on consumer loyalty, 4). Price discount variable (X2) with consumer loyalty (Y2) is proven to have an effect and is significant on consumer loyalty, 5). Consumer satisfaction variable (Y1) with consumer loyalty (Y2) proved to have a significant effect on consumer loyalty.